Recycling of Basalt and Limestone Cutting Dust in Concrete Mix Design - Mohammad T. Awwad; Ashraf Shaqadan; Jamal Al-Adwan; Faroq Maraqa (Civil Engineering Journal, 2023)
Objectives: The goal is to integrate stone cutting waste into the concrete manufacturing industry to reduce environmental degradation. Methods/Analysis: Two types of stone cutting waste (Basalt and limestone) were separately collected from local facilities. An experimental program was conducted to prepare concrete mixes with 10%, 20%, 30%, and 40% replacement of sand by the two types of stone powder. Physical and chemical quality testing was carried out on the water, aggregates, and cement used in the concrete mix. The experiment compared a standard concrete mix (0% replacement) consisting of 6 cylinders and 6 cubes with a mix of 24 cylinders and 24 cubes after 7 days and 28 days. Results: Compression, tension, and stress tests were performed on the produced specimens. Regarding basalt replacement, a 10% replacement showed a higher impact on compressive strength and tension. For limestone, the 10% and 40% replacement fractions exhibited an insignificant reduction in compressive strength, indicating that a 40% replacement of sand with limestone dust is practical for most applications. Replacing sand with stone cutting waste in concrete can bring several benefits to the environment and enhance project feasibility. Even a small fraction of replacement can improve concrete properties. Novelty:Protect natural sand mining causes damage to ecosystems, leading to erosion and loss of biodiversity. Doi: 10.28991/CEJ-2023-09-05-010 Full Text: PDF